Bibliometric analysis of publications related to the pharmaceutical supply chain before and after the Covid-19 pandemic in the period 2010-2021 - Sovero Castro, Lucia Isabel (2022)
The pharmaceutical industry has undergone changes in the management of its logistics processes, making it vulnerable to disruptions such as the Covid-19 pandemic. This study compares the scientific production on the pharmaceutical chain during the period 2010-2021, divided into two periods, through a bibliometric review of research indexed in Scopus and Web of Science. The main authors, institutions, countries, journals and thematic areas are identified, and the studies of greatest scientific relevance are analyzed. The VosViewer tool is used to visualize the relationships between authors and between keywords. A total of 785 publications related to the pharmaceutical chain were identified during 2010-2021. The institutions with the highest publication activity were concentrated in Iran, Morocco and Saudi Arabia. Co-authorship and keyword co-occurrence analyses show the main authors and research topics in both periods. Research on the pharmaceutical chain has been increasing in recent years, but few relate to COVID-19.